Market Based Approach in Clean Cooking Solutions in Kenya &Tanzania - Muok, Benard (JOOUST, 2020)
The project aim at evaluating and developing strategies for catalysing the diffusion and adoption of clean cooking solutions in East Africa with focus in Kenya and Tanzania
Keywords: Clean Gass; Clean Cooking